Making conceptual connections visible to students in professional programmes: The case of initial teacher education - Rusznyak, L (South African Journal of Higher Education, 2016)
This paper presents a comparative analysis of education courses offered across five South African universities participating in the Initial Teacher Education Research Project. The analysis compares knowledge selected for compulsory education modules that are taken by all student teachers regardless of their subject / phase specializations. All programmes include modules that examine curriculum knowledge, learners, pedagogy and context as objects of study in their own right. However, these objects are studied through different practical and/or theoretical lenses. The extent to which each object is brought into relation with others is also variable and programme design structures suggest that these relationships will be explored in specialization courses. However, it should not be presumed that this will happen without explicit collaboration and coordination. It is recommended that the relations between the elements need explicitly to be designed into the compulsory courses, subject/phase specific pedagogy courses and in the design of the practicum.